Mesopotamian Gods and the Bull - Dijk-Coombes, Renate Marian van (2018)
In Mesopotamia, gods were associated with the bull from at least the Early Dynastic Period until the Neo-Babylonian or Chaldean Period. This relationship took on many forms – the bull could serve as the god’s divine animal, the god could be likened to the bull, or he could actually take on the form of the beast. In this paper, the various gods identified with or related to the bull will be identified and studied in order to identify which specific types of god were most commonly and especially associated with the bull. The relationships between the gods and the bull are evident in textual as well as iconographic sources, although fewer instances of this connection are found in iconography. Examples of the portrayal of the association between the various gods and the bull in texts and iconography can be compared and contrasted in order reveal differences and similarities in these portrayals.